The effective compatible in-service training: a structured review of literature - Mahmood Chaghary; Abbas Ebadi; Mohsen Saffari; Ahmad Ameryoun; Mohammad Soltani (Tehran University of Medical Sciences, 2016)
Background & Aim: Undoubtedly, the knowledge and skills of the employees lead to the survival of the organization. The purpose of this study is to investigate the important issues in designation and implementation of staff in-service training models to determine a framework for designing the efficient nursing continuing education models. Methods & Materials: This study is a structured review based on Cochrane five-step protocols, in which18 qualitative articles from six English, and three Persian databases were extracted and analyzed using seven-step process of Noblit and Hare method in meta-synthesis without any limit of time. The English databases included "Science Direct, PubMed, Google Scholar, EBSCO, Proquest, and SAGE Journals" and Farsi databases were "Noormags, Iran Doc, and SID." A standardized protocol along with specified criteria was used to study selection. Results: In the initial analysis of findings four themes were extracted: process for staff training, method for staff training, educational effectiveness, and specific model for staff training. The final analysis of findings showed that the models presented in the field of staff training can be generally divided into three categories: (a) Models that deal with the designation of processes and functions of staff training, (b) models that focus on the effectiveness of staff training, and (c) models that deal with both aspects. Conclusion: This study highlights the important role of effectiveness strategies as well as compatible training functions in designing the nursing staff in-service training models. In this way, the staffs motivate to participate actively in the organizational trainings.